Impact of music intervention on psychological and physiological parameters of patients undergoing myocardial perfusion scintigraphy - Vieira, Lina Oliveira (2024)
Aim/Introduction: Myocardial Perfusion Scintigraphy (MPS), a well-established imaging procedure for diagnosing ischemic heart disease, has multiple phases that can induce patients’ anxiety, discomfort, and dissatisfaction. Several non-pharmacological strategies have been used to alleviate anxiety and improve patient comfort and satisfaction, such as music intervention. This study aimed to evaluate the efficacy of musical intervention in the outcomes of patients undergoing MPS. Materials and Methods: A randomized clinical trial was conducted on patients undergoing an MPS one-day protocol stress-rest, in a Nuclear Medicine Department between January 15, and March 18, 2024. Patients were divided into a control group (CG) and an experimental group (EG). In the EG, a musical intervention was performed during the rest image acquisition, allowing patients to choose from a selection of musical tracks curated by a music lecturer. Anxiety levels were assessed at four different moments in both groups: before and after the stress image acquisition (T1 and T2), and before and after the rest image acquisition (T3 and T4), using physiological parameters at all times and psychological parameters for CG at T1 and T4 and for EG at T1, T3 and T4. Image quality analysis was performed using measures of contrast, noise, number, and amplitude of patients' movements. All studies were reviewed by two researchers and evaluated by three nuclear medicine technologists. Results: The sample comprised 30 participants with an average age of 71±11.02yrs [45-87yrs] with 15 participants enrolled in each group. Patients in EG reduced their anxiety scores from 36±9.44 at T1 to 33±7.07 at T3 and 28±9.11 at T4, while patients in CG reduced their anxiety scores from 39±10.62 at T1 to 33±9.66 at T4. Regarding patient motion, there was a reduction from the CG to EG in movements between 1-2 pixels (CG = 21, EG= 19) and movements higher than 2 pixels (CG =19, EG=6). In some myocardial walls on the three tomographic slices, the correlation between psychological parameters and image noise was lower in T4 for the EG. No significant results were found in image contrast. Conclusion: For the EG, the image noise was ~3% lower than in CG. Anxiety decreased throughout the MPS procedure with lower values at T4 for the EG. Additionally, the musical intervention seems to be effective as the EG showed lower values of patient movement.